A dança nas aulas de Educação Física: legitimidade e democratização ‘via’ prática pedagógica - Altoe, Janaina Lubiana (2020)
This paper is the result of a pedagogical intervention proposal developed in the State High School Emílio Nemer, located in Castelo (ES). The main concern is to rethink dance as a subject of the high school Physical Education program by using analyses, ap